Politiche linguistiche sovranazionali, nazionali e locali. La regolamentazione della comunicazione nello spazio pubblico in Europa, in Italia, nel Lazio e a Roma Capitale - Oricchio, Alessandro (Studi Politici, 2023)
In recent decades, the language issue has emerged more forcefully within the political debate, also according to the new needs arising from the rapid evolution of contemporary societies, which are configuring themselves as increasingly mobile, fluid, multicultural and multilingual contexts. The management of the linguistic element, therefore, has become a priority, as linguistic phenomena play a decisive role in the construction of the social and cultural reality. This article, after a brief discussion of the concepts of language planning and language policy, aims to offer an overview of the main language policy interventions in the supranational, national, regional and local dimensions, delving, then, into the last two dimensions by focusing on two case studies regarding the regulation of public space communication: the Lazio Region and the city of Rome.